Changes in macro‐ and micronutrient contents of grasses and forbs following Miscanthus x giganteus feedstock, hydrochar and biochar application to temperate grassland. (5th February 2015) - Schimmelpfennig, S.; Kammann, C.; Moser, G.; Grünhage, L.; Müller, C.
Abstract Biochar and hydrochar application to soil holds promise for climate change mitigation. This study provides first insights into the nutrient concentration and removal of grassland vegetation after addition of various carbon compounds together with pig slurry. Four treatments: control (no carbon application), feedstock, hydrochar and biochar from Miscanthus x giganteus were applied at a permanent grassland site near Giessen, Germany. Changes in plant functional groups, biomass production and nutrition status were monitored over 2 years. Total biomass production was not affected by the carbon amendments. However, biochar favoured growth of forbs over grasses, while legume growth was increased by all carbon amendments. The initial nutrient concentrations of the carbon compounds were enriched according to their degree of carbonization, potentially providing nutrients to plants. The plant biomass from hydro‐ and biochar amended plots, added up over 2 years, exhibited higher potassium concentrations compared to biomass from feedstock and control plots. All carbon amendments led to lower sodium concentrations in total biomass, compared to the control. Uncarbonized feedstock led to increased manganese concentrations in total biomass, while the concentrations of all other heavy metals were not influenced by any carbon amendment, compared to the control. From a plant and animal nutritional point of view, none of the carbon amendments reduced grassland yield or fodder quality. The study suggests that hydrochar and, even more so, biochar may provide a source of potassium to plants.